Plantar pressure distribution using personalised 3D printed lattice insoles with distributed stiffness - Siegkas, Petros; Lane, Charlie; Apps, Charlotte (My University, 2024)
This work presents a proof-of-concept study on the use of additive manufacturing for developing customised lattice topology insoles, with the aim of redistributing plantar pressures. Four cubic lattice structures were applied to five sections of the moulded insole contours, which were based in 3D foot scans using Ansys material designer to predict material properties. The variation of the elastic modulus across the sections was controlled via the lattice cell structure volume ratio. The insole lattice structures were made from elastic photosensitive liquid resin resulting in flexible parts. A commercially available shoe was used to compare pressure distribution between the original and customised insole. Plantar pressure distribution and peak pressures were measured during standing, walking, and running. Pressure redistribution varied between insole conditions. During standing, the customised insole reduced peak pressure at the left heel, while the right foot experienced increased peak pressure compared to the control insole. Substantial peak pressure reduction was observed on the left foot during walking and running whilst the reduction was much less for the right foot. The study highlights the potential of additive manufacturing for cost-effective, accurate, and personalized insole production, offering material control and pressure redistribution benefits for various applications like injury prevention and rehabilitation.
Keywords: 3D Printing; additive manufacturing; functionally graded; insole; material designer; personalised; plantar pressure